Exploring senior high school student's abilities in mathematical problem posing - Muhtarom, Muhtarom; Shodiqin, Ali; Astriani, Novita (JRAMathEdu (Journal of Research and Advances in Mathematics Education), 2020)
The ability of problem posing is very essential for the student’s. However, there are still many students who don't realize the importance of these abilities. This research describes the senior high school student’s ability in mathematical problem posing, especially in the material system of linear equations in three variables. Research data were collected from 7 student’s using written test and interview techniques. The validity of the data used triangulation methods by comparing the results of written tests and interviews. Data were coded, simplified, presented, and triangulated for the credibility and conclusion drawing. The results show that there were still very few students who have all three classifications of problem posing abilities, namely pre-solution posing, within-solution posing, and post-solution posing. Students who have the ability of pre-solution posing can ask questions based on the data provided and can arrange problem solving. Students who have the ability of within-solution posing can write what is given and asked of the problem, raise supporting questions which is relevant to the problem and arrange solutions to the supporting questions and problems that are given correctly. Students who have the ability of post-solution posing can raise similar mathematics problem after solving the problem. Students can also arrange solutions to problems that have been made. Teacher needs to practice pre-solution posing, within-solution posing, and post-solution posing to the students.